Foreign tourists as homicide victims in Croatia: a routine activity approach - Mataković, Hrvoje (International e-journal of criminal sciences, 2023)
The safety of tourists is of great importance in tourism-oriented countries such as Croatia, and the most serious threat to tourists is homicide. This paper examines the factors that have led to the homicides of foreign tourists in Croatia. For this analysis, the routine activity theory approach and its three key elements are used: a motivated offender, a suitable target, and the absence of a capable guardian. As there is no official data on crimes against foreign tourists in Croatia, the analysis was conducted using data from the media. The data for the analysis were collected using a questionnaire with 18 variables that can be divided into three groups: offender characteristics, victim characteristics, and the circumstances of the offence. The analysis showed that three factors had the strongest influence on the commission of foreign tourists’ homicides: they got into disputes with unknown or little-known people; they consumed alcohol with people they did not know well; and they were alone in an unknown environment, far from the police or other people who could help them.